PENGARUH WORKPLACE BULLYING TERHADAP TURNOVER INTENTION YANG DIMEDIASI OLEH WORK ENGAGEMENT PADA ANGGOTA UNIT KEGIATAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Audivia Monica; Megawati Megawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to measure the effect of workplace bullying to turnover intention with work engagement as the mediating variable at the member of  Student Activity Unit, Economics and Business Faculty, Syiah Kuala University. The sample used in this study was member of Student Activity Unit, Economics and Business Faculty, Syiah Kuala University Involving 151 respondents. Instrument used for data collecting was questionnaire. Simple random sampling was used as the sampling technique. Partial Least Square (PLS)  was used as analysis method to determine the effect of variables involved. Based on the analysis results, it is indicated that workplace bullying influence turnover intention and work engagement, work engagement influence turnover intention as well as work engagement partially mediate the relationship between workplace bullying and turnover intention.